Improving Students’ Speaking Ability Through Story Telling Technique - Nunung Nurhayati (Papanda Publisher, 2022)
This final project about improving students speaking ability through story telling technique at the tenth grade of SMKN 1 Maja . Teaching speaking at high school have many problem and most of student still have difficulties in speaking. It caused by some factors, those are : students are too shy and afraid to take a part in conversation, students are still clumsy in speaking, and students are not enthusiastic and not courage enough to involve in the speaking learning process . The objectives of this research are to know how the students’ speaking ability before and after teaching by using story telling technique and to find out the effectiveness of story telling technique in improving students’ speaking ability. While the hypothesis are: Null hypothesis (Ho) : Story telling technique is not effective in teaching speaking to improve students’ speaking ability and Alternative hypothesis (Ha) : Story telling technique is effective in teaching speaking to improve students’ speaking ability. This research uses the pre experimental research with one group as eksperimental and control. The population in this field is the 360 students of tenth grade of SMKN 1 Maja. The samples are 29 students. To get the analyzable data, the researcher uses three procedures, pre-test, treatment and post-test. While to collecting data technique, researcher uses the pre-test, observation check-list, field-notes and post-test. Based on the finding of pre-test, the researcher find the achievement of student in average 55,86. Based on the observation check list, the average score of students in treatment were very good. And the result of the post-test 63,44 The achievement of the students in learning speaking through this way was improved. It was supported by the significant result of the test. The average achievement of the students pre-test, 55,86. And the post test result was 63,44. It indicates that there is an effect using story telling to improve student’s speaking ability at tenth grade of SMKN 1Maja. The teaching procedure that researcher build in teaching speaking with using story telling technique are as follows: 1) Pre-speaking activity: greeting, praying, checking the attendance, showing the picture related to the topic, make prediction about the text, give questions about the topic, explain the topic, distributing worksheet. 2) Whilst-speaking activity: reading the text and answer the question from the text, identifying the generic structure, make short story and tell the story . 3) Post-speaking activity: giving feedback, reflection, homework and saying farewell. The conclusion of this research is students’ achievement in speaking ability before teaching by using story telling technique is low, while students’ speaking ability after teaching by using story telling technique is improve. Finally the story telling technique is effective in improving the students’ speaking ability. The result of this research are expected to give contributions to the development of English speaking teaching and learning process, especially to headmaster, English teachers, and future researchers. (1). For the headmaster, the results can be beneficial regarding to improve the educational quality. (2). For the English teachers, the result are expected as a input data about the using of story telling in teaching English. (3). For the next researchers, the results are expected the study will be beneficial and helpful for the future researchers as their guide.